Acolhimento aos imigrantes haitianos nas Unidades Básicas de Saúde do Município de Medianeira/PR à luz da Política Nacional de Humanização – HumanizaSUS - Kukul, Ivandro Marcelo (2025)
Migration is a topic that requires knowledge and sensitivity. In many Brazilian cities, there are immigrants and refugees hoping for a new home and decent living conditions. This reality can be seen not only in Brazil, but in many other countries, which can be attributed to the shortening of distances that the world has witnessed in recent decades. This thesis will focus on the theme of Haitian immigrants, these people who, after a series of political and environmental crises in their homeland, saw no alternative but to migrate to Brazil and chose, among many other places, the city of Medianeira/PR in search of employment and quality of life. The choice of the topic is linked to the need for health professionals to take a different view of this new profile of users of the Unified Health System (SUS). We chose to investigate whether the city‟s Basic Health Units are prepared to provide humane care to this segment of the population, which has unique characteristics that are different from Brazilians, in terms of ethnic, linguistic, cultural and socioeconomic aspects. This is precisely the issue of humane care, which is the subject of this thesis. Since Haitian immigrants are constitutionally treated on an equal footing with Brazilians, they deserve the same treatment, under conditions of equality, comprehensive and universal, in all areas of health. Therefore, the general objective is to understand whether the ministerial policy called HumanizaSUS is applied in the care of Haitian immigrants. We understand that providing care to Haitian immigrants requires a differentiated, sensitive and committed perspective on the part of health professionals who work in primary care or in other areas of the SUS. To this end, the specific objectives are: 1. To investigate the migration process based on the events that worsened the situation of the Haitian population after 2010; 2. To present the National Policy for Humanization in Health implemented in Brazil since 2003; 3. To identify how Haitian immigrants are welcomed in the UBSs of the municipality of Medianeira/PR and whether there is a protocol to guide the actions of professionals who work in welcoming these “new SUS users”. For this purpose, an exploratory research was chosen, whose theoretical methodological model is of a qualitative nature and which proposes discourse analysis, according to the categorization of the results obtained. After analyzing the theoretical framework on the theme, the following research question was reached: Do the Basic Health Units of the Municipality of Medianeira/PR have a reception protocol for Haitian immigrants? To answer the question, semi-structured interviews were conducted with the coordinating and assistential nurses of the eleven UBSs of the municipality in question, during the year 2024, with a total of fourteen professionals being interviewed. The main categories that were the object of data analysis emerged from the investigation, and were distributed as follows: a) Communication: the language barrier in welcoming Haitian users; b) Cultural barriers; c) The preparation of the team to welcome Haitian immigrants: the need for training for the staff; d) Informational and economic vulnerability of Haitian patients; e) Reception and the National Humanization Policy: the little or no knowledge on the part of the health teams. In view of the results obtained, this thesis suggested the creation of a specific protocol for Haitian immigrants, to be developed jointly by the professionals working in the city's Health Units, and the institution of a continuing education program for public health workers, as a permanent education, where issues regarding Haitian immigrants and humanized reception will be addressed, in order to minimize the main difficulties identified during the investigation.